STUDI ANALISIS KOPEL ANTARA METODA ELEMEN BATAS DAN METODA ELEMEN HINGGA PADA STRUKTUR PORTAL-DINDING GESER - Wibowo (NIM 25099011), Ari
Abstract : In this study, numerical investigation is carried out to investigate coupled analysis between finite element method (fern) and boundary element method. We take frame-shear wall as an object of analysis. Boundary element method has some advantages : (1) Simplicity in element discritisation process, (2) High accuracy of stress which less number of elements, (3) Element order is one level simpler than finite element. But finite element method has advantage in linear algebra equation solver. Stiffness matrices of, finite element is symmetry and bandwidth form, so the efficient solver can be used, e.g. bandwidth storage. In other side, boundary element influence matrices has fill matrices and not symmetry, so direct method has to be used, e.g. gauss elimination. For the frame-shear wall case, frame is modelled as beam-column finite element, and shear wall is modelled as plane stress boundary element. The result show that displacements and internal stress have high accuracy, but less efficient than pure fem. Coupled analysis in this case has to use partial analysis and not full analysis, so the assembly of force matrices and equivalent stiffness matrices need iterative gauss elimination process, so time operation is not efficient.